The Application of Ideological and Political Thinking in College English - Weihong Zhao, Xiaoge Wang, Yafei Chen (Forest Chemicals Review, 1970)
Under the "great ideological and political thinking" pattern, the "ideological and political thinking of College English" will be incorporated into the overall planning, in order to improve the ideological, political or theoretical level of English in private colleges or universities, promote transformation of the ideological, political concept of "four cultural integration". To enhance the "ideological, political thinking of English in colleges", the concept of "four cultural integration", we should combine knowledge imparting with morality, and build an innovative moral system in colleges or universities, provide reference for concrete operation of "ideological, political thinking" of college English in private universities.